Recognizing an Islamic Hero: The Quran-Hadith's Vision about Muhammad al-Fatih In Indonesian Comics - D.I. Ansusa Putra (Universitas Islam Negeri Mataram, 2022)
This study highlights the different Qur'an-Hadith visions regarding Islamic heroism in the Muslim community, especially in Indonesia. The lack of attention of Islamic scholars to the concept of heroism was significant, emphasized by analyzing the heroism of Muhammad al-Fatih in Indonesian Islamic comics, using the socio-heroism theory of Kristian Frisk. Critical discourse analysis reviews the relation of the Qur'an-Hadith visions in the Muhammad al-Fatih comic with the social discourse of heroism in Indonesia. Furthermore, this study concludes that Islamic heroism is recognized based on two aspects, namely the transcendental recognition from the information of the Qur'an-Hadith vision and the inherent recognition from the Muslim community. It also discovered that Islamic comics in Indonesia introduce the heroism of Muhammad al-Fatih due to several factors and objectives. First is the long-standing relationship with the Turkish community. Second, the Islamic heroism in Muhammad al-Fatih's actions is considered a sign of Islamic glories and brilliance. Third, his victory is considered by some groups as an example and a positive role model for Muslims from various aspects. Therefore, this research will significantly contribute to the knowledge of future Islamic scholars about Islamic heroism, the Quran-Hadith vision, and the study of religious comics, especially in Indonesia.